DESAIN MEDIA PEMBELAJARAN BAHASA INGGRIS UNTUK SISWA TUNARUNGU BERBANTUAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Marzal, Jefri (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
Understanding words is one the language components that becoming a problem for students with hearing impairment â€“ students with hearing and speaking problem. This difficulty exists because student with hearing impairment do have any perception about language. The difficulties of student with hearing impairment in understanding words will consequently causing problem for them in understanding and delivering sentences in written language and to interact in hearing community. The main goal of this research is to develop a media teaching and learning English based on Information Communication and Technology (ICT) and Edmodo â€“ social network media that used exclusively as e-Ââ€learning tool, toward the ability of hearing impairment students in understanding meaning of words, semantic, and their interaction in learning English. The research also investigated the effectiveness of using the media in learning English for the students. The result shows that students with hearing impairment are very motivated in understanding words and sentences taught assisted with ICT and Edmodo. The everyday classroom interaction shows that the students are actively participating in individual and group works. In addition, students have a good perception about teaching assisted with ICT and Edmodo. Keyword: ICT and Edmodo, Hearing Impairment Students, Teaching and Learning English